Aptamer nucleotide analog drug conjugates in the targeting therapy of cancers - Li, Yongshu; Zhao, Jing; Xue, Zhichao; Tsang, Chiman; Qiao, Xiaoting; Dong, Lianhua; Li, Huijie; Yang, Yi; Yu, Bin; Gao, Yunhua (Frontiers in Cell and Developmental Biology, 2022)
Aptamers are short single-strand oligonucleotides that can form secondary and tertiary structures fitting to targets with high affinity and specificity. They are so-called ‘chemical antibodies’ and can target specific biomarkers in both diagnostic and therapeutic applications. Systematic Evolution of Ligands by Exponential Enrichment (SELEX) is usually used for the enrichment and selection of aptamers and the targets could be metal irons, small molecules, nucleotides, proteins, cells, even tissues or organs. Thanks to the high specificity and distinctive binding affinity of aptamers, aptamer-drug conjugates (ApDCs) demonstrated their potential role in drug delivery for cancer targeting therapies. Comparing with antibodies which are produced by cell-based bioreactor, aptamers are chemical synthesized molecules that can be easily conjugated to drugs and modified. But the conventional ApDCs are conjugated the aptamer with active drug by a linker which may increase the more concerns to the stability of the ApDC, the drug releasing efficiency as well as the drug loading capacity. It is just treat aptamer as a targeting moiety which could not fully perform the advantages of aptamers. To address these drawbacks, scientists have started to employ active nucleotide analogues as the cargoes of ApDCs, such as clofarabine, ara-guanosine, gemcitabine, and floxuridine, to replace the all or part of natural nucleotides in aptamer sequences. In turn, this new type of ApDCs, aptamers nucleotide analogue drugs conjugates, own the strength for targeting efficacy but avoid the complex drug linker designation and improve the synthetic efficiency. More importantly, these classic nucleotide analogue drugs have been used for many years, and aptamer nucleotide analogue drug conjugates would not increase any unknown druggability risk but improve the target tumor accumulation. In this review, we mainly summarized aptamer conjugated nucleotide analogue drugs in cancer targeting therapies.